Boistimulator effect of stress tolerant rhizobacteria on horticultural models - Gerőcs, A.; Alshaal, T.; Fári, M.; Domokos-Szabolcsy, É. (International Journal of Horticultural Science, 2014)
The tolerant bacteria for abiotic stresses such salinity, drought, and different pH have been used as a good tool to improve plant growth in sustainable agriculture. A pot experiment was conducted to evaluate the potential of isolated stresstolerant bacteria for red mud-polluted soil on growth performance of giant reed plants with increasing concentrations of NaCl 0.0; 0.1; 0.2; 0.3; 0.5; 1.0% under gnotobiotic conditions. At the same time biostimulator potential of isolated bacteria was observed in case of radish in vitro germination experiment under salt stress. It was found that the observed bacterial strain can tolerate the salt and pH moderately however it is resistant against hydrogen-peroxide caused oxidative stress in high concentration (up to 2640 mM). Molecular identification, basis on 16S rDNA showed 98% similarity to the Bacillus aryabhattai bacterial strain. The isolated strain alleviated the negative effect of salt (0.05%) for the radish seed germination. However in higher salt concentration (≥0.1%) the bacterial mitigating effect vanished. The inhibition of increasing salt concentration for giant reed plantlets was also alleviated by halotolerant bacteria treatment (≥0.5%).